Carbon Dioxide Electroreduction using a Silver–Zinc Alloy. Issue 6 (9th March 2017) - Hatsukade, Toru; Kuhl, Kendra P.; Cave, Etosha R.; Abram, David N.; Feaster, Jeremy T.; Jongerius, Anna L.; Hahn, Christopher; Jaramillo, Thomas F.
Abstract: We report on CO2 electroreduction activity and selectivity of a polycrystalline AgZn foil in aqueous bicarbonate electrolyte. X‐ray photoelectron spectroscopy (XPS) and X‐ray diffraction (XRD) measurements show that the alloy foil was slightly enriched in zinc both at the surface and in the bulk, with a surface alloy composition of 61.3±5.4 at % zinc and with Ag5 Zn8 as the most prominent bulk phase. AgZn is active for CO2 reduction; CO is the main product, likely due to the weak CO binding energy of the surface, with methane and methanol emerging as minor products. Compared to pure silver and pure zinc foils, enhancements in activity and selectivity for methane and methanol are observed. A five‐fold increase is observed in the combined partial current densities for methane and methanol at −1.43 V vs. the reversible hydrogen electrode (RHE), representing a four‐ to six‐fold increase in faradaic efficiency. Such enhancements indicate the existence of a synergistic effect between silver and zinc at the surface of the alloy that contributes to the enhanced formation of further reduced products. Abstract : Multi‐metal synergy ! High CO2 electroreduction activity and selectivity are reported on a polycrystalline AgZn foil in aqueous bicarbonate electrolyte. Compared to pure Ag and pure Zn foils, enhancements in activity and selectivity for methane and methanol are observed. Such enhancements indicate the existence of a synergistic effect between Ag and Zn at the surface of the alloy that contributes to the enhanced formation of further reduced products.